2019
DOI: 10.1002/ece3.4939
|View full text |Cite
|
Sign up to set email alerts
|

A fine‐scale phylogenetic assessment of digenean trematodes in central Alberta reveals we have yet to uncover their total diversity

Abstract: Despite over 100 years of digenean trematode parasite species descriptions, from a wide diversity of vertebrate and invertebrate host species, our ability to recognize the diversity of trematode species within a single lake remains an incredible challenge. The most challenging aspect is the identification of species from larval stages derived from intermediate hosts, due to the disjointed data of adult worm morphological descriptions, from which species are named, and links to corresponding molecular identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(95 citation statements)
references
References 71 publications
(150 reference statements)
5
88
0
Order By: Relevance
“…The collection of trematode cercariae from their snail first intermediate hosts in central Alberta has been previously described ( Gordy et al, 2016 ), as were the methods used for species identifications through molecular and morphological assessments ( Gordy et al, 2017 ; Gordy and Hanington, 2019 ), thus we only summarize the key findings here. The final dataset from this survey resulted in 2452 trematode samples that ultimately represented 79 trematode species identified from infections within five freshwater snail species: Stagnicola elodes, Lymnaea stagnalis, Helisoma trivolvis, Physa gyrina, and an unidentified planorbid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The collection of trematode cercariae from their snail first intermediate hosts in central Alberta has been previously described ( Gordy et al, 2016 ), as were the methods used for species identifications through molecular and morphological assessments ( Gordy et al, 2017 ; Gordy and Hanington, 2019 ), thus we only summarize the key findings here. The final dataset from this survey resulted in 2452 trematode samples that ultimately represented 79 trematode species identified from infections within five freshwater snail species: Stagnicola elodes, Lymnaea stagnalis, Helisoma trivolvis, Physa gyrina, and an unidentified planorbid.…”
Section: Methodsmentioning
confidence: 99%
“…The final dataset from this survey resulted in 2452 trematode samples that ultimately represented 79 trematode species identified from infections within five freshwater snail species: Stagnicola elodes, Lymnaea stagnalis, Helisoma trivolvis, Physa gyrina, and an unidentified planorbid. The collections took place from June to September 2013–2015 on a biweekly basis across six lakes in central Alberta: Buffalo Lake, Gull Lake, Isle Lake, Lac La Nonne, Pigeon Lake, and Wabamun Lake (for specific site information, see Gordy et al, 2016 ; Gordy and Hanington, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, Heneberg et al [13] has combined a morphological and molecular analysis of central European Strigeidae from avian de nitive hosts to investigate the taxonomic position of several Cotylurus species and surprisingly revealed a high level of molecular diversity within morphologically wellestablished species. Locke et al [31] and Gordy and Hanington [14] also revealed the occurrence of several new species within this genus in Canada. These results clearly indicate the need for further, detailed morphological, molecular and phylogenetic studies.…”
Section: Introductionmentioning
confidence: 90%
“…Since then, the taxonomic status and validity of these genera have been questioned and changed several times: some authors (e.g., [17,18]) reduced Australapatemon to the level of a subgenus within Apatemon, while Yamaguti [19] restored it to the full generic rank, as further con rmed by Niewiadomska [20]. As the morphological differences between Apatemon and Australapatemon in both metacercariae as well as adult specimens are limited or subtle, these taxa have often been incorrectly determined (for details see [6] and references therein), and thus a few attempts to use molecular markers in the identi cation, taxonomy and phylogeny of these genera have been made in recent years [21,22,6,12,14,23]. Importantly, a detailed molecular analysis of cercariae and adult specimens of Australapatemon sampled across North America clearly indicates the existence of several distinct lineages within this taxon and indisputably points out the hidden species diversity [12,14].…”
Section: Introductionmentioning
confidence: 99%